Business Process Analysis and Improvement during Covid-19 Crisis: a Case of Frozen Shrimp Manufacturer - Hechaipoom Sasita (EDP Sciences, 2021)
Frozen shrimp is one of the major export products of Thailand. This research studied a frozen shrimp products supply chain, which is a large-sized manufacturer in central Thailand. Our objectives were to study the current supply chain of a frozen shrimp processor in Samut Sakhon province and propose suggestions to improve efficiency in each activity, especially to cope with the Covid-19 crisis. First, we analyzed its business process by using Integration Definition for Function Modeling (IDEF0) to investigate the stakeholders in the supply chain and the business process of the frozen shrimp manufacturer. After analysis, we identified problems and proposed how to improve efficiencies such as risk management, especially for shrimp and labor shortage. The supplier relationship should be established along with the contract, forecast price, and demand for shrimps to optimize the procurement. The labor should be trained for multi-skill and lean production should be applied to increase productivity. Finally, digitization should be fully transformed and set up the centralized information to reduce time, increase accuracy and share the data with partners. In summary, our guidelines for the frozen shrimp manufacturer could be applied to similar manufacturers to improve supply chain efficiency.